(untitled) (Dhaka University Journal of Science, 2012)
In order to achieve a better understanding of how scanning tunneling microscopy (STM) images of metallo-complexes are related to the geometric and electronic structure, we performed scanning microscopy (STM) and scanning tunneling spectroscopy (STS) techniques on [FeIIIFeIII 3L6] (L= N-methylaminediethanolate) star-type tetranuclear molecular magnet. The experiments were performed under ambient condition. We were able to image single molecule by STM with submolecular resolution. In our STS measurements we found a rather large signal at the positions of iron ion centers in the molecules. This direct addressing of metal centers was further confirmed by density functional theory (DFT) calculations. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10343 Dhaka Univ. J. Sci. 60(1): 87-91 2012 (January)